1997
DOI: 10.1172/jci119545
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal peptide prevents excitotoxic cell death in the murine developing brain.

Abstract: Excitotoxic damage may be a critical factor in the formation of brain lesions associated with cerebral palsy. When injected at birth, the glutamatergic analog ibotenate induces mouse brain lesions that strikingly mimic human microgyria. When ibotenate is injected at postnatal day 5, it produces transcortical necrosis and white matter cysts that mimic human perinatal hypoxic-like lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
122
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(134 citation statements)
references
References 54 publications
11
122
0
1
Order By: Relevance
“…Every third section was stained with cresyl violet. Previous studies (Gressens et al, 1997;Husson et al, 2002) have shown an excellent correlation between the maximal size of the lesion in the lateralmedial and fronto-occipital axes of the excitotoxic lesions. Based on these findings, we cut serial sections of the entire brain in the coronal plane for this study.…”
Section: Excitotoxic Lesions and Lesion Size Determinationmentioning
confidence: 74%
See 1 more Smart Citation
“…Every third section was stained with cresyl violet. Previous studies (Gressens et al, 1997;Husson et al, 2002) have shown an excellent correlation between the maximal size of the lesion in the lateralmedial and fronto-occipital axes of the excitotoxic lesions. Based on these findings, we cut serial sections of the entire brain in the coronal plane for this study.…”
Section: Excitotoxic Lesions and Lesion Size Determinationmentioning
confidence: 74%
“…To test it, we used a well characterized mouse model of neonatal excitotoxic brain lesions (Marret et al, 1995;Gressens et al, 1997;Dommergues et al, 2000;Tahraoui et al, 2001;Husson et al, 2002), which mimic lesions observed in preterm and term human infants who will later develop CP. In this model, intracerebral administration of glutamate analogs acting on NMDA or non-NMDA receptors replicates the excess release of glutamate induced, among others, by hypoxic-ischemic insult (Volpe, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Newborn mice injected intracerebrally with ibotenate, a glutamate analog acting mainly on N-methyl-D-aspartate (NMDA) receptors, develop periventricular cystic white-matter lesions mimicking several aspects of human PVL (10). In this well characterized murine model, several drugs that interfere with the excitotoxic cascade have been shown to be neuroprotective (7,(11)(12)(13)(14) while proinflammatory cytokines (15) and iron (16) exacerbated ibotenateinduced white-matter lesions. In order to further understand the pathophysiology of the ibotenateinduced cystic lesions, we targeted the NMDA receptors thought to be present on white-matter glial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Based on epidemiological and experimental studies, the pathophysiology of PVL appears to be multifactorial. It potentially involves the combined toxicity of hypoxic-ischemic insults, excess free radicals, maternal-fetal infection with increased cytokine production, and growth factor deficiency (1,(3)(4)(5)(6)(7)(8). Excess release of glutamate and the subsequent overactivation of the excitotoxic cascade could represent a common molecular pathway for several of these risk factors (6, 9).…”
mentioning
confidence: 99%
“…PACAP on the other hand represses antigen presenting cell activities initiated by macrophages and dendritic cells (Kato et al, 2004). In the CNS these anti-inflammatory reactions induced by VIP and PACAP are protective in the MS environment where anti-inflammatory reactions are minimal Gressens et al, 1997). Additionally damaged neurons of the CNS may release VIP and PACAP perhaps as a restorative mechanism, in an attempt to rescue homeostasis in the CNS and this has been confirmed by down regulation of molecules such as, TNF-a, IL-6, IL-1 and overactive microglia .…”
Section: Multiple Sclerosismentioning
confidence: 99%